On the Dimension of the Solution Set for Semilinear Fractional Differential Inclusions - Ravi P. Agarwal; Bashir Ahmad; Ahmed Alsaedi; Naseer Shahzad (Abstract and Applied Analysis)
We investigate the existence and dimension of the solution set for a nonlocal problem of semilinear fractional differential inclusions. The main tools of our study include some well-known results on multivalued maps.